Identifying Biomarkers for Remyelination and Recovery in Multiple Sclerosis: A Measure of Progress - Ricigliano, Vito A G; Marenna, Silvia; Borrelli, Serena; Camera, Valentina; Carnero Contentti, Edgar; Szejko, Natalia; Bakirtzis, Christos; Gluscevic, Sanja; Samadzadeh, Sara; Hartung, Hans-Peter; Selmaj, Krzysztof; Stankoff, Bruno; et al. (Biomedicines, 2025)
Background: Multiple sclerosis (MS) pathology is characterized by acute and chronic inflammation, demyelination, axonal injury, and neurodegeneration. After decades of research into MS-related degeneration, recent efforts have shifted toward recovery and the prevention of further damage. A key area of focus is the remyelination process, where researchers are studying the effects of pharmacotherapy on myelin repair mechanisms. Multiple compounds are being tested for their potential to foster remyelination in different clinical settings through the application of less or more complex techniques to assess their efficacy. Objective: To review current methods and biomarkers to track myelin regeneration and recovery over time in people with MS (PwMS), with potential implications for promyelinating drug testing. Methods: Narrative review, based on a selection of PubMed articles discussing techniques to measure in vivo myelin repair and functional recovery in PwMS. Results: Non-invasive tools, such as structural Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET), are being implemented to track myelin repair, while other techniques like evoked potentials, functional MRI, and digital markers allow the assessment of functional recovery. These methods, alone or in combination, have been employed to obtain precise biomarkers of remyelination and recovery in various clinical trials on MS. Conclusions: Combining different techniques to identify myelin restoration in MS could yield novel biomarkers, enhancing the accuracy of clinical trial outcomes for remyelinating therapies in PwMS.
Keywords: multiple sclerosis; recovery; remyelination; biomarkers